Recommendations for skin cancer consultation and surgery during COVID‐19 pandemic. (12th August 2020) - Brochez, L.; Baurain, J.F.; Del Marmol, V.; Nikkels, A.; Kruse, V.; Sales, F.; Stas, M.; Van Laethem, A.; Garmyn, M.
Abstract : Linked articles : COVID‐19 SPECIAL FORUM. J Eur Acad Dermatol Venereol 2020; 34 : e433–e466 .